All-Cause Health Care and Work Loss Burden Associated With Nonsteroidal Anti-Inflammatory Drug and Opioid Treatment in Employed Patients With Osteoarthritis. Issue 8 (21st August 2022) - Silverman, Stuart; Thakkar, Sheena; Sell, Heather; White, Alan G.; Downes, Nathaniel; Pajerowski, William; Robinson, Rebecca L.; Beck, Craig G.; Emir, Birol; Schepman, Patricia
Abstract : NSAIDs, tramadol, and non-tramadol opioids are the most commonly prescribed medications to treat OA-related pain. Our study examined the impact of these drug treatments among employed patients with OA in terms of changes in all-cause healthcare resource utilization and costs, as well as work loss outcomes. Abstract : Introduction: This study estimated all-cause health care resource utilization (HRU) and costs and work loss outcomes associated with pain management of employed patients with osteoarthritis of the hip and/or knee. Methods: Optum Health Care Solutions data were analyzed for employed patients prescribed nonsteroidal anti-inflammatory drugs, tramadol, or nontramadol opioids following diagnoses of osteoarthritis of the hip and/or knee. A pre-post design was used to evaluate changes in all-cause HRU and costs, and work loss days and associated costs. Results: Costs rose for patients in all three cohorts (up to 198.3% for health care costs [tramadol] and up to 178.7% for work loss costs [tramadol]). Greatest increases in all-cause HRU included inpatient visits (237.9% [nonsteroidal anti-inflammatory drugs]; 600% [tramadol]). Conclusions: Study results provide evidence of increases in all-cause HRU and costs and work loss days and associated costs.